Carbon Emission Disclosure and Eco-Efficiency on Firm Value: Analysis of Indonesian Energy Companies Moderated by Foreign Ownership - Ghazi Abiyyu Alsammy Delizar; Lidiyawati (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Climate change and global warming are issues currently being faced by the world. Extreme temperature changes and the increasing intensity of natural disasters that occur throughout the world are the main causes of news about global warming being increasingly hotly discussed. Increasing human activities have resulted in higher carbon dioxide levels, along with the increasing use of fossil fuels such as oil and natural gas, and coal. This study aims to report how the implementation of carbon emission disclosure (CED) and eco-efficiency affect company value, and whether or not there is a moderating effect of foreign ownership on the relationship between CED and eco-efficiency on company value. Carbon emission scores are measured using 18 measurement lists based on data from the company's annual report, while eco-efficiency is assessed based on the existence of certification in its sustainability report. The research sample was 23 energy sector companies out of 80 companies listed on the IDX from 2020-2022. The list of criteria was created in order to meet the depth of insight about carbon emissions and eco-efficiency. The regression results show that CED disclosure can significantly increase company value. In contrast eco-efficiency could not increase firm value significantly, but more than 85% of companies have been certified throughout the observation period. Although the foreign ownership variable cannot play a significant role as a moderating variable, its influence coefficient is positive and increasing. Overall, the findings show results that are consistent with signal theory and stakeholder theory.